Яичко: [потешная сказка] / А. Елисеев ; ил. автора - Елисеев Анатолий (ЭНАС-КНИГА, 2012)
Для дошкольников. Экземпляры: Д. Б. (20230208) / Инвентарный номер: 49705 / Цена: 198.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: 84(2Рос=Рус)6 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6